Strengthening the Capacity of Partnership-Based Cultural Heritage Management to Increase Tourism Visits - Titi Darmi; Iqbal Miftakhul Mujtahid; Ledyawati Ledyawati (Publik : (Jurnal Ilmu Administrasi), 2021)
This article discusses the extent to which Cultural Heritage management involving various sectors can contribute to increasing tourist visits. The research was conducted in the city of Bengkulu, the location of the research was the legacy of Bung Karno's house. Data collection was carried out through secondary data and primary data. Primary data was carried out by interviewing related parties, namely two of Bung Karno's house staff, the Head of the Jambi Cultural Heritage Preservation Agency (BPCB), the Head of the Bengkulu Province Education Office, one cultural expert, four tourism activists, and six communities. members who were visiting Bung Karno's house. The steps in this research are data collection, classification, analysis, and data processing, making conclusions, then narrating in depth. The results of the study explain that the Heritage of Bung Karno's House is one of the historical tourist objects visited by many tourists. Bung Karno's heirloom house is a historical tourism object that has an attraction and has an important role in increasing tourist visits. For optimal Cultural Heritage management, it is important to strengthen the capacity of Cultural heritage management sustainably by optimizing technology and involving five partnership sectors, namely government, private sector, universities, media, and society.